Patient-reported outcome measures used to improve youth mental health services: a systematic review - Kalpana Thapa Bajgain; Mungunzul Amarbayan; Krystle Wittevrongel; Erin McCabe; Syeda Farwa Naqvi; Karen Tang; Fariba Aghajafari; Jennifer D. Zwicker; Maria Santana (SpringerOpen, 2023)
Abstract Background Patient-reported outcome measures (PROMs) are standardized and validated self-administered questionnaires that assess whether healthcare interventions and practices improve patients' health and quality of life. PROMs are commonly implemented in children and youth mental health services, as they increasingly emphasize patient-centered care. The objective of this study was to identify and describe the PROMs that are currently in use with children and youth living with mental health conditions (MHCs). Methods Three databases (MEDLINE, EMBASE, and PsycINFO) were systematically searched that used PROMs with children and youth < 18 years of age living with at least one diagnosed MHC. All methods were noted according to Preferred Reporting Items for Systematic reviews and Meta-Analysis. Four independent reviewers extracted data, which included study characteristics (country, year), setting, the type of MHC under investigation, how the PROMs were used, type of respondent, number of items, domain descriptors, and the psychometric properties. Results Of the 5004 articles returned by the electronic search, 34 full-texts were included in this review. This review identified both generic and disease-specific PROMs, and of the 28 measures identified, 13 were generic, two were generic preference-based, and 13 were disease-specific. Conclusion This review shows there is a diverse array of PROMs used in children and youth living with MHCs. Integrating PROMs into the routine clinical care of youth living with MHCs could improve the mental health of youth. Further research on how relevant these PROMs are children and youth with mental health conditions will help establish more uniformity in the use of PROMs for this population.